Design and Fabrication of a Capacitance Based Wearable Pressure Sensor Using E-textiles. (2015) - Arogbonlo, A.; Usma, C.; Kouzani, A.Z.; Gibson, I.
Abstract: This paper addresses the methods used for the design and fabrication of a capacitance based wearable pressure sensor fabricated using neoprene and (SAC) plated Nylon Fabric. The experimental set up for the pressure sensor is comprised of a shielded grid of sensing modules, a 555 timer based transduction circuitry, and an Arduino board measuring the frequency of signal to a corresponding pressure. The fundamental design parameters addressed during the development of the pressure sensor presented in this paper are based on size, simplicity, cost, adaptability, and scalability. The design approach adopted in this paper results in a sensor module that is less obtrusive, has a thinner and flexible profile, and its sensitivity is easily scalable for 'smart' product applications across industries associated to sports performance, ergonomics, rehabilitation, etc.